Intersectional feminist criminology: A critical companion to theory and research - Michalsen, Venezia (University of California Press, 2025)
This pathbreaking book brings to bear a sweeping body of contemporary intersectional feminist work to disrupt the entire discipline of criminology. Women have been largely absent from criminological theory, research, policy, and practice. This fresh, conversational book critiques the field's dominant theories by analyzing gendered patterns of perpetration and victimization and challenging traditional criminological perspectives on characteristics such as race and queerness. Designed as a rebuttal to conventional criminology textbooks, the book mirrors standard course content through an intersectional feminist lens, offering students a valuable opportunity to question the field's underpinnings and forge a new path to understanding the true meaning of justice. Organized in fourteen chapters, each chapter includes accessible learning aids for students: A review of how traditional criminology textbooks cover the topic. Critical perspectives on the topic. Critical thinking breaks. Intersectional Feminist Criminology is a timely intervention and companion to the curriculum that helps to imagine a new world and ultimately lays out a clear abolitionist vision as an alternative to the American criminal legal system. © 2025 by Venezia Michalsen. All rights reserved.
Keywords: dept.soc